Experimental study of seismic in-plane elliptical damper with empirical design formulae. Issue 8 (11th August 2021) - Lee, Chien-Liang; Chen, Yung-Tsang; Cai, Meng-Yan; Wang, Yen-Po
Abstract : A seismic steel damper designed to deform inelastically in an in-plane flexural bending mode for more efficient utilisation of the material was investigated. This proposed device, referred to as an in-plane elliptical damper (i-PED), consists of two circular arches with intermediate straight arms connected in a closed form to eliminate end rotation at the symmetric axis in order to enhance the ultimate capacity. Test results obtained from a series of component tests on i-PEDs with various dimensions indicated that the energy-dissipation capacities of the dampers under cyclic loads were rich and consistently stable. The i-PED with a shorter arm length and smaller radius of curvature of arch exhibited higher strength and energy-dissipation capacity. Empirical formulae for estimating the mechanical properties of the dampers were developed for preliminary design purposes. The numerical predictions were found to correlate well with the experimental results, demonstrating that using the Bouc–Wen model is sufficient for simulating the inelastic mechanical behaviour of steel dampers. Furthermore, shaking table tests of a five-storey modal frame implemented with i-PEDs were conducted, with non-linear time history analyses carried out for comparison. Encouraging results on seismic response control with good numerical prediction were obtained, suggesting the feasibility of the proposed damper and design scheme for practical application.